The Needs Analysis of Teachers and Students towards the Online Comic as the Learning Media - Berlian, Mery; Vebrianto, Rian; Thahir, Musa (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2023)
This research aims to analyze the needs of teachers and students towards the online comic as the learning media. This research is a survey research with a qualitative descriptive approach. The sample in this study was 417 people consisting of 323 students, 55 teachers and 39 lecturers who were taken by stratified sampling and random. The research data was obtained from distributing questionnaires through google form and analyzed using the percentage formula. The findings obtained were: 1) 69.15% of teachers and 58.15% of students often use the audio-visual as the learning media; 2) the characteristics of the online comics that have been used by teachers and students have met good criteria with a percentage of 80.91%; 3) 84.04% of teachers and 74.92% of students have never used online comics as the learning media; 4) 93.26% of teachers and 92.26% of students are interested in using online comics as the learning media; 5) 97.87% of teachers and 97.52% of students want online comic designs to have a color combination; 6) 97.87% of teachers and 89.16% of students want a story in the form of a dialogue text. From the results of the study, it reveals that the online comics are needed as a media of learning among teachers and students. All in all, the research results can be used as information for researchers, further researchers or teachers in general as a reference for developing or using the learning media.